EFEKTIFITAS METODE SELEKSI MASSA PADA POPULASI BERSARI BEBAS JAGUNG MANIS - Elfiani, Elfiani (DINAMIKA PERTANIAN, 2017)
One method that can be used in the assembly of sweet corn is a method of mass selection. The purpose of this study was to determine the progress of mass selection in a population of open pollinated sweet corn based on the character of plant height and diameter of the cob without cornhusk. The study was conducted in July – Desember 2009 at the Garden experiment IPB Gunung Gede, Bogor. Plant materials used are pollinated population of maize orange wrinkle-open generation of mass selection of the second selection result from six different strain of corn. Selection is done by using three kinds of methods: (1) choose 10% of individual plants directly the total population, (2) selecting 10% of individuals from each plot are then combined to obtain the data of 10% of the total population and (3) selecting swath middle value greater equal to the total population of middle and then selecting individual plants 10% of the population. Mass Selection method to select populations in plots give a higher genetic progress than other methods. Plant height can be used as selection criteria in the selection of high differential value in the character length and diameter of the cob.